A COMPREHENSIVE REVIEW ON IN VITRO ANTHELMINTIC ACTIVITIES OF SOME AYURVEDIC PLANTS - Bora, *Manajit; Kawlni, Lalrinpuia; Upadhyay, Sachchidanand; Mukherjee, Koyel; Hazra, Jayram (International Journal of Ayurveda and Pharma Research, 2017)
Ayurveda, the Science of life, commonly uses medicinal plants for treating various diseases. Numerous medicinal plants are being used traditionally for treating parasitic infections in India. In Ayurveda, worm infestation in the gastro intestinal tract is known as Krimi roga. Many Ayurvdeic medicinal plants are used traditionally for treating Krimi roga. Use of synthetic drugs anthelmintic for treating parasitic infestations causes serious toxic side effects in human. Use of Ayurvedic plants has no such side effects and, economical. The paper highlights anthelmintic activities of some of the most important Ayurvedic medicinal plants carried out in vitro in various pharmacological models. A brief review of In vitro anthelmintic activities of thirteen Ayurvedic medicinal plants published by various researchers is illustrated in this paper. The medicinal plants discussed here are Vidanga: Embelia ribes Burm. F, Kalmegh: Andrographis paniculata (Burm.f.) Nees, Gunja: Abrus precatorius L., Kiratatikta: Swertia chirata L., Khadira: Acacia catechu (L.f.) Willd., Ativisha: Aconitum heterophyllum Wall. ex Royle, Saptaparna: Alstonia scholaris (L.) R. Br., Aragvadha: Cassia fistula L., Nimba (Azadirahcta indica A. Juss.), Brahmi: Bacopa monnieri (L.) Penn., Mandukaparni: Centella asiatica (L.) Urban, Vacha: Acorus calamus L. and Chirbhita: Carica papaya L.